Biliary tract and liver complications in polycystic kidney disease - Judge, P; Harper, C; Storey, B; Haynes, R; Wilcock, M; Staplin, N; Goldacre, R; Baigent, C; Collier, J; Goldacre, M; Landray, M; Winearls, C; et al. (American Society for Nephrology, 2017)
Polycystic liver disease is a well-described manifestation of autosomal dominant polycystic kidney disease (ADPKD). Biliary tract complications are less well-recognised. We report a 50-year single-centre experience of 1,007 patients, which raised a hypothesis that ADPKD is associated with biliary tract disease. This was then tested using all-England Hospital Episode Statistics data (1998-2012) within which 23,454 people recorded as having ADPKD and 6,412,754 hospital controls were identified. Hospitalisation rates for biliary tract disease, serious liver complications and a range of other known ADPKD manifestations were adjusted for potential confounders and then compared. Compared to non-ADPKD hospital controls, the rates of admission for biliary tract disease were 2.2-times higher in those with ADPKD (rate ratio [RR] 2.24, 95% confidence interval 2.16-2.33) and 4.7-times higher for serious liver complications (RR 4.67, 4.35-5.02). When analyses were restricted to those on maintenance dialysis or with a kidney transplant, RRs attenuated substantially, but ADPKD remained positively associated with both biliary tract disease (RR 1.19, 1.08-1.31) and with serious liver complications (RR 1.15, 0.98-1.33). The ADPKD versus non-ADPKD hospital control RRs for biliary tract disease were larger for men than women (heterogeneity p<0.001), but RRs for serious liver complications appeared higher in women (heterogeneity p<0.001). The absolute excess risk of biliary tract disease associated with ADPKD (0.73%/year) was larger than for serious liver disease (0.24%/year), cerebral aneurysms (0.11%/year), or inguinal hernias (0.11%/year), but less than for urinary tract infections (2.20%/year). Biliary tract disease appears to be a distinct and important extra-renal complication of ADPKD.